1976
DOI: 10.1007/bf03005693
|View full text |Cite
|
Sign up to set email alerts
|

An index of syndromes and their anaesthetic implications

Abstract: PATIENTS often present for anaesthesia and surgery having been "labelled" with a diagnosis of some eponymous or rare syndrome. This index is an attempt to catalogue as many syndromes as possible which have anaesthetic implications and to give an indication of their main features.It is hoped that it will be useful as a ready reference especially for those involved in paediatric anaesthesia, as many of these patients present in infancy or childhood.The information is presented in tabular form with a cross index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…On the other hand, Matsuda et al [6] reported a 3-year-old male with trisomy 18 who was scheduled for fixation of the testicle and developed muscular rigidity after administration of succinylcholine. Endotracheal intubation became impossible [7]. The patient was managed under mask anesthesia and had a high temperature (38.4~ and an elevated creatine phosphokinase level during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Matsuda et al [6] reported a 3-year-old male with trisomy 18 who was scheduled for fixation of the testicle and developed muscular rigidity after administration of succinylcholine. Endotracheal intubation became impossible [7]. The patient was managed under mask anesthesia and had a high temperature (38.4~ and an elevated creatine phosphokinase level during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Children with cranial nerve palsies and weakness of the ocular muscles may present for correction of the resultant strabismus and orthopaedic procedures are also common due to the limb anomalies. There is little in the anaesthetic literature on the implications of this rare syndrome, other than unreferenced referrals to the possibility of difficult intubation with affected children (Jones & Pelton 1976). This paper sets out to review the past 15 years' experience of anaesthesia and Moebius syndrome in a tertiary paediatric teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Orofacial malformations are also common. These malformations include micrognathia, microstomia, tongue-tethering and premaxillary overgrowth (Jones 1988;Gorlin 1990). Other anomalies with anaesthetic implications which occur more frequently in Moebius syndrome include congenital cardiac disease (Carvella & Rogers 1978;Bosch-Banyeras et al 1984), cervical spine anomalies (Bouwes-Bavinck & Weaver 1986), peripheral neuropathies (Rubenstein et al 1975;Abid et al 1978) and pectoral muscle deficiencies (also known as Poland syndrome) (David 1972).…”
Section: Introductionmentioning
confidence: 99%
“…It may be the first anaesthesia for the newborn or infant and previously unrecognized syndromes may become apparent at this time. Primary assessment, past history and, if a syndrome is present, the anaesthesia implications thereof should be evaluated prior to induction of anaesthesia (Jones & Pelton 1976). In the case report under discussion the anaesthetic history indicated previous difficulty and the possible need for an alternative anaesthetic technique.…”
mentioning
confidence: 99%